PENGARUH KUALITAS PELAYANAN DAN PROMOSI TERHADAP KEPUASAN PELANGGAN PADA KEDAI MIE AYAM & BAKSO WONOGIRI MAS WANTO DI TANGERANG SELATAN - Widya Febry Nurika; Kris Dipayanti (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
The purpose of the study was to determine the effect of service quality and promotion on customer satisfaction at Mie Ayam Bakso Wonogiri Mas Wanto in South Tangerang. The type of research is associative, with a quantitative approach. As for. The population is customers in 2023 as many as 6,046 people, sampling can use the slovin formula, so the sample is 98 customers. Data analysis using validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficient analysis, determination coefficient analysis and hypothesis testing, The results of the study show that service quality (X1) and promotion (X2) have a positive and significant effect on customer satisfaction (Y) with the regression equation y = 13.444 + 0.380x1 + 0.378x2. the correlation coefficient value of 0.784 means that it has a very strong relationship, the determination coefficient is 0.614 or 61.4% while the remaining 38.6%. influenced by other factors not examined in this study. Partial hypothesis test obtained positive service quality value t count> t table or (5.333> 1.985) then Hο is rejected and H1 is accepted, this indicates that there is a significant influence between service quality and customer satisfaction. Partial hypothesis test obtained promotion positive value t count> t table or (6.828> 1.985) then Hο is rejected and H2 is accepted, this indicates that there is a significant influence between promotion and customer satisfaction. The results of the F hypothesis test obtained F count> F table or (75.668> 2.70). This is also reinforced by a significance value of 0.000 <0.05. Thus it can be concluded that service quality and promotion together or simultaneously have a positive and significant effect on customer satisfaction. Keywords: Service Quality, Promotion, Customer Satisfaction